Mecanismos de estabilidad de políticas públicas fallidas : el caso de la política de lucha contra las drogas en Colombia (2017)
In spite of the high economic and social costs of the fight against drugs in Latin America, the constant calls for a deep reform of the strategy have not succeeded in generating major changes in politics. The same happens with many policies, which have become true slot machines in the countries and, as with the fight against drug trafficking, do not reflect great advances in the solution of the problem. But how do governments manage to maintain public policies that are ineffective? To fulfill the purpose of solving the question, in the document, public policy is not going to be analyzed as a product of the governmental organization, nor through the description of the policy cycle. Rather, under the assumptions of causal mechanisms and a relational ontological framework (Tilly, 2001), public policy is understood as a political process, which is the result of the development of the forces of cooperation and conflict materialized in a set of differentiated relations of power that occur within the space of public policy. In order to do so, a historical institutional framework is used, from which it is argued that the mechanisms of self-reinforcement are those that allow the subsystem actors to have the necessary resources to maintain the policy, even though it is not functional, and it allows to the policies initiate sequential dynamics of conditioning of decisive government behavior. To verify this, a case study is carried out through Process Tracing, which demonstrates the different periods and mechanisms used to reinforce the trajectory of the policy. The work shows that there have been different types of reinforcement mechanisms that have allowed, according to the type of threat of change and the scenario of the policy, to counteract the transformation pressures.--Tomado del Formato de Documento de Grado.